2004
DOI: 10.1637/7148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Mycoplasma gallisepticum Isolates from Turkeys

Abstract: Mycoplasma gallisepticum was isolated from several turkey flocks at different locations in the United States that were clinically affected with respiratory disease. Five of these isolates from four series of outbreaks had patterns similar to the 6/85 vaccine strain of M. gallisepticum by random amplified polymorphic DNA (RAPD) analysis using three different primer sets, whereas with a fourth primer set (OPA13 and OPA14), only two of the isolates were similar to 6/85. Results obtained by sequencing portions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Further experiments will be needed to examine strain differences in tissue tropism and the initial sites of colonization. Previous studies have detected thickening only of the upper tracheal mucosa in turkeys exposed to M. gallisepticum by aerosol, possibly because this was the only section of the trachea examined Kleven et al, 2004;Zaki et al, 2004). However, we demonstrated that thickening of the mucosa could be detected along the length of the trachea.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Further experiments will be needed to examine strain differences in tissue tropism and the initial sites of colonization. Previous studies have detected thickening only of the upper tracheal mucosa in turkeys exposed to M. gallisepticum by aerosol, possibly because this was the only section of the trachea examined Kleven et al, 2004;Zaki et al, 2004). However, we demonstrated that thickening of the mucosa could be detected along the length of the trachea.…”
Section: Discussioncontrasting
confidence: 58%
“…However, none of these studies used the same criteria to assess infection and disease, so it is difficult to compare the different routes of inoculation that were used. Lin & Kleven (1982) assessed gross air sac lesions and serology, Dingfelder et al (1991) examined reisolation and serological responses, Kleven et al (2004) reported re-isolation, serology, air sac and upper tracheal lesion scores and measurement of upper tracheal mucosal thicknesses, and Sanei et al (2007) assessed serology, reisolation, air sac lesions, clinical signs, tracheal mucosal lesions and thicknesses at three levels of the trachea. There have also been studies that demonstrated the safety of the K5054, ts-11 and 6/85 strains in turkeys and their capacity to protect against air sac lesions and increases in tracheal mucosal thickness caused by exposure to a coarse spray of the R strain Zaki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the use of live MG vaccines, it is important to be able to differentiate the vaccine strain from MG wild strains. The most widely used methods to differentiate MG strains are the immunoblot polyacrylamide gel electrophoresis of mycoplasma proteins (Bencina et al, 1994), the random amplified polymorphic DNA analysis (Geary et al, 1994;Fan et al, 1995;Charlton et al, 1999), restriction enzyme analysis (Kleven et al, 1988;Liu et al, 2001) and the sequence analysis of MG genes (Liu et al, 2001;Kleven et al, 2004).…”
Section: Abstract: Mycoplasma Gallisepticum Vaccine Rapd Pcr Pcr-mentioning
confidence: 99%
“…This research was complemented with the examination of MG strains using primers specific for different genes with published sequences such as gapA and pvpA (Liu et al, 2001;Kleven et al, 2004). In addition, in our study PCR tests were designed to amplify for different fragments of crmA, crmB, crmC, gapA and mgc2 genes, respectively.…”
Section: Abstract: Mycoplasma Gallisepticum Vaccine Rapd Pcr Pcr-mentioning
confidence: 99%
See 1 more Smart Citation